Analisis Perencanaan Strategis, Rencana Strategis dan Manajemen Strategis STAIN Curup 2015-2019 - Warlizasusi, Jumira (Institut Agama Islam Negeri (IAIN) Curup, 2018)
The strategics plan is a guideline for a short plan.the strategic plan isn’t as holy as the holy book till it couldn’t be changed.depend on the route record of this strategics plan,it can be evaluated.for it implementation, RKA oftenly not according to the strategic plan. even it found that RKA is more priority than the strategic plan.so it considered like useless thing and it only needed if it necessary. component of agency performance appraisal, and the proo of the documentation for evidence it’s realistic as same as planned (has a track record exist). Arranging the strategic plan of STAIN Curup process during 2015-2019 it started with mapping the activities until 2014. besides of this situation, it could be known all of the troubles and the defiances which it has influence the functions and the main assignment. more over, it needed the analysis about the influence of strategic environment which it involved. even it direct or indirect, with main assignment or a function, although it internal or external. the influence of internal strategic would be trasformated into the strength and the weakness, so the influence of external strategic will be transformating into the opportunities and the treath. By considering of this influence environment strategic change, it propose the rules of wisdom to reach the performance’s target inside arranging strategic plan of STAIN Curup 2015-2019. to clear the main assignment and it function’s way, the vision it would be formulated and described into yhe mission side.based on vision and mission, it formulated the purpose , target, priority,strategy and the wisdom’s way. The strategic plan of STAIN Curup in 2015-2019 need to analyzed for get the understanding complex has been reached. began from analyzing the strategic planning, strategic plan and strategic management, analyzing design of organization as the initial supply to plan the strategic, analyze of building the capability of natural resource and evolving structural organization, analyze the payment and suspension organization system,analyze of matching the internal process and learn process in an organization,analyze centralization and decentralization inside strategic management,analyze the strategic when control and analyzing management change and organization learners. Keywords: Strategic Planning, Strategics Plan, Strategic Management